Improving Chronic Pain Management Processes in Primary Care Using Practice Facilitation and Quality Improvement: The Central Appalachia Inter-Professional Pain Education Collaborative - Roberto Cardarelli; Sarah Weatherford; Jennifer Schilling; Dana King; Sue Workman; Wade Rankin; Juanita Hughes; Jonathan Piercy; Amy Conley-Sallaz; Melissa Zook; Kendra Unger; Emma White; et al. (Journal of Patient-Centered Research and Reviews, 2017)
Purpose: With the increasing burden of chronic pain and opioid use, provider shortages in Eastern Kentucky and West Virginia have experienced many challenges related to chronic pain management. This study tested a practice facilitator model in both academic and community clinics that selected and implemented best practice processes to better assist patients with chronic pain and increase the use of interdisciplinary health care services. Methods: Using a quasi-experimental design, a practice facilitator was assigned to each state’s clinics and trained clinic teams in quality improvement methods to implement chronic pain tool(s) and workflow processes. Charts for 695 patients with chronic pain using opioids, from 8 randomly selected clinics in eastern Appalachia, were reviewed to assess for changes in clinic processes. Results: Statistically significant improvements were found in 10 out of 16 chronic pain best practice process measures. These included improved workflow implementation (P < 0.001), increased urine drug screen test orders (P = 0.001) and increased utilization of controlled medication agreements (P = 0.004). In total, 7 of 8 clinics significantly improved in at least one, if not all, selected and implemented process measures. Conclusions: Our findings indicate that practice facilitation, standardization of workflows and formation of structured clinical teams can improve processes of care in chronic pain management and facilitate the use of interdisciplinary services. Future studies are needed to assess long-term patient-centered outcomes that may result from improved processes of chronic pain care.